2015
DOI: 10.1074/jbc.m114.621730
|View full text |Cite
|
Sign up to set email alerts
|

La-related Protein 1 (LARP1) Represses Terminal Oligopyrimidine (TOP) mRNA Translation Downstream of mTOR Complex 1 (mTORC1)

Abstract: Background: mTORC1 plays an important role in the regulation of TOP mRNA translation. Results: LARP1 is a target of mTORC1 that associates with TOP mRNAs via their 5ЈTOP motif to repress their translation. Conclusion: LARP1 represses TOP mRNA translation downstream of mTORC1. Significance: We elucidate an important novel signaling pathway downstream of mTORC1 that controls the production of ribosomes and translation factors in eukaryotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
370
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(419 citation statements)
references
References 100 publications
(100 reference statements)
48
370
0
1
Order By: Relevance
“…However, LARP1 activity by itself seems insufficient to explain 5′TOP-mediated translation, as a recent study found that LARP1 interacts with a broad class of approximately 3,000 mRNAs that include most but not all 5′TOP-containing transcripts 131 . Moreover, there is evidence that LARP1 binding to the 5′TOP may actually repress translation rather than activate it 132 . Further studies using unbiased approaches, such as comprehensive identification of RBPs by MS (CHIRP-MS) to identify physiologically relevant RBPs and in vivo click-SHAPE (icSHAPE) to identify RNA structure, are needed to fully elucidate the underlying mechanisms of this and other translational elements and to move towards a comprehensive understanding of how mRNA structure and sequence synergize to write the translational code.…”
Section: Sequence-specific Rna Elementsmentioning
confidence: 99%
“…However, LARP1 activity by itself seems insufficient to explain 5′TOP-mediated translation, as a recent study found that LARP1 interacts with a broad class of approximately 3,000 mRNAs that include most but not all 5′TOP-containing transcripts 131 . Moreover, there is evidence that LARP1 binding to the 5′TOP may actually repress translation rather than activate it 132 . Further studies using unbiased approaches, such as comprehensive identification of RBPs by MS (CHIRP-MS) to identify physiologically relevant RBPs and in vivo click-SHAPE (icSHAPE) to identify RNA structure, are needed to fully elucidate the underlying mechanisms of this and other translational elements and to move towards a comprehensive understanding of how mRNA structure and sequence synergize to write the translational code.…”
Section: Sequence-specific Rna Elementsmentioning
confidence: 99%
“…In contrast, a more recent study proposed that active mTORC1 interacts with LARP1 and inhibits LARP1’s function to suppress translation initiation of LARP1-interacting 5’TOP mRNAs (Fonseca et al, 2015). Thus, the functional importance of LARP1-mTORC1 interaction and the role of LARP1 in the regulation of translation of LARP1-interacting mRNAs remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the length of the 5 ′ UTR, rather than the presence of a TISU, is the primary factor that determines EIF4E-versus EIF4A1-sensitivity. mTORC1 modulates translation of TOP mRNAs via LARP1 (Tcherkezian et al 2014;Fonseca et al 2015), whereas synthesis of mitochondrial, proliferation-and survival-promoting proteins is controlled by the EIF4EBP/EIF4E pathway (Larsson et al 2012;Morita et al 2013). Notably, 5…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, the effects of serum deprivation on TOP mRNA translation also appeared to be EIF4E-independent (Shama et al 1995). In turn, LARP1 and TIA1/TIAL1 (also known as TIAR) were reported to mediate effects of mTORC1 on TOP mRNAs (Damgaard and Lykke-Andersen 2011;Tcherkezian et al 2014;Fonseca et al 2015). Polysome-profiling showed that the mTORC1/EIF4EBP axis also regulates translation of non-TOP mRNAs, including those encoding mitochondrial and survivaland proliferation-promoting proteins (Larsson et al 2012;Morita et al 2013).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%